ROSZCZENIA PIENIĘŻNE W SPRAWACH O OCHRONĘ AUTORSKICH PRAW MAJĄTKOWYCH - Kot, Dawid (Wydział Prawa i Administracji UAM, 2003)
The Polish Copyright Act provides for a number of claims for copyright protection, including pecumiary claims i.e. claims seeking money payment. There are two claims falling under this category in article 79 sections 1 and 2. The first of them is a claim to pay a multiple salary (double or, in cases of culpable violation, triple remuneration at the time of making the claim). The other one, payable to the Art Promotion Fund by the person who committed a violation within the business activity performed on his own or another person’s behalf, payable even to somebody else’s account in the amount of at least double the probable benefits incurred by the violating party as a result of the violation. The Act also mentions claims to return the benefits incurred and claims to redress injuries committed in a culpable act. These claims can have either a pecuniary or non-pecuniary character (return of benefits in kind or redressing injuries by restoration of the former state). Such interpretation of the character of these claims results from respective provisions of the Polish Civil Code concerning unjust enrichment (art. 405) and redressing injuries (art. 363), but this interpretation can also be applied to the currently binding Act, irrespective of the view concerning the relation between claims under the Act and claims under the Civil Code. In the doctrine there is a dispute whether the claim to return incurred benefit, which is secured by consecutive copyright acts can be considered an unjust enrichment claim as understood in the civil code or rather a separate claim different in nature. The civil code appears to emphasise the non-pecuniary character of the unjust enrichment claim and claim for redressing injuries, since it primarily quotes return in kind (art. 405) and redressing injuries by restoration of the former state (art. 363 §1 sentence 1). It may appear, however, that in copyright cases claim for return of benefits incurred and claim for redressing injuries will never have a non-pecuniary form due to the intangible character of the protected good. This is not entirely the case, however. It has long been known that such a claim to return incurred benefits in kind is an adjudicative claim i.e. one that seeks an adjudication granting the copyright bearer the objects that were subject to violation. The preceding copyright acts mentioned only unlawfully produced copies of work but at present under art. 80 section 3 such a claim can be applied only to objects used for unlawful production of copies of work or any other objects other than copies of work that were used for the violation. However, this claim is presently classified by definition as a non-pecuniary claim to remove the results of the violation, despite the fact that there are no sufficient grounds for such a claim in the Act in the area o f economic rights. Although such grounds is sometimes seen in art. 80 section 5, this provision can also be treated as a procedural counterpart of adjudicative claim taken from the material law. Such an adjudicative claim, when interpreted as a claim to remove the results of the violation rather than, alternatively, a claim to return the benefits incurred, fails to have sufficient legal grounds in the Act. On the other hand, it may be argued that the category of a claim for redressing injuries i.e. restitution claim includes a claim to render harmless, in particular to destroy the objects used for the purpose of unlawful production of copies of the protected work or any objects other than copies of the work that were used for the purpose of the violation. Also this claim seems to be a form of the by definition non-pecuniary claim to remove the results of the violation. Alternatively, it may also be seen as a (non-pecuniary) claim for desistence, clearly indicated in the Act among the claims available in cases of copyright violation (art. 79 section 1 in principio). It is therefore possible to include within the category of pecuniary claims only those claims for return of benefits or for redressing injuries that are based on a return of the benefit value and redressing injuries through payment, which will prove dominant in the case of copyright protection. With the above assumption the list of pecuniary claims resulting from the Copyright Act includes the following: • Claim to return benefits incurred, • Claim to pay multiple remuneration, • Claim to pay at least double probable benefit value; • Claim for redressing injuries. All the above claims can be accumulated except for the first two, which occur separately due to deeper historical reasons.
PECUNIARY CLAIMS IN COPYRIGHT CASES